Comparing the effects of climate change labelling on reactions of the Taiwanese public - Li-San Hung (Nature Portfolio, 2020)
Terms such as ‘climate change’ and ‘climate crisis’ need to be evaluated for their effectiveness for public perception. In this study of a sample of the Taiwanese public reactions to the terms were largely the same, however, in specific subgroups the term ‘climate crisis’ faced some backlash.